LOW-PRESSURE METAMORPHISM AND LEUCOGRANITE MAGMATISM, NORTHEASTERN YEONGNAM MASSIF, KOREA: IMPLICATION FOR PALEOPROTEROZOIC CRUSTAL EVOLUTION - Kim J.; Cho M. (My University, 2003)
The northeastern Yeongnam Massif consists primarily of pelitic to psammopelitic metasedimentary rocks, together with garnet-bearing leucogranites and granitic gneisses. Metapelitic mineral assemblages define three progressive metamorphic zones of the low-pressure facies series: cordierite, sillimanite, and garnet zones with increasing temperature. Metamorphic grade ranges from lower-amphibolite to lower-granulite facies, reaching 750–800 °C and 4–6 kbar in migmatitic gneisses. Geochemical characteristics, such as the enrichments of Rb and Ba relative to Sr, high K contents, and negative εNd (1.9 Ga) values, indicate that peraluminous leucogranites were produced primarily by the fluid-absent melting of supracrustal rocks. Trace element characteristics of leucogranites are generally compatible with those of volcanic arc granites, and the widespread crustal melting may be attributed largely to magmatic heat flux in an arc environment. Whole rock Pb–Pb ages suggest that leucogranite intruded at ca. 1.93–1.86 Ga into the granitic gneiss, formed by an earlier magmatic episode at ca. 1.95 Ga. These ages are compatible with those of felsic magmatism reported from other parts of the Yeongnam Massif. Our results, in conjunction with the available geochronologic data, suggest that four stages of Precambrian crustal evolution are represented in the Yeongnam Massif: (1) the formation of proto-crust at ca. 2.9–2.5 Ga, and felsic magmatic episodes primarily at (2) ca. 2.1 Ga, (3) 1.95 Ga, and (4) 1.9 Ga. In particular, the last tectonothermal event produced widespread low-pressure type metamorphism in association with the emplacement of leucogranite, and is correlative with the Luliangian Orogeny in North China.
Keywords: Yeongnam Massif; LP/HT metamorphism; Leucogranite; Paleoproterozoic; Pb–Pb and Sm–Nd ages; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская